Longitudinal Relationship Between Self-Esteem and Academic Self-Efficacy Among College Students in China: Evidence From a Cross-Lagged Model - Luo, Yunfeng; Gao, Wenjuan; Liu, Xinqiao (Frontiers in Psychology, 2022)
The present study aimed to investigate the associations between self-esteem and academic self-efficacy among Chinese college students. Descriptive statistics showed that on average, students’ academic self-efficacy experienced a downward trend in the first three years before rising slightly in the graduation year, and that male students had higher academic self-efficacy than females in the first two years, whereas female students’ academic self-efficacy surpassed their male counterparts in the latter years. There were significant, positive associations between the two variables. With cross-lagged analysis, we found that students’ self-esteem significantly predicted their subsequent academic self-efficacy from the freshman to the junior years, and the effects among male students endured longer and stronger. Implications of the findings were discussed.